1976
DOI: 10.1172/jci108250
|View full text |Cite
|
Sign up to set email alerts
|

Lung collagen heterogeneity. Synthesis of type I and type III collagen by rabbit and human lung cells in culture.

Abstract: A B S T R A CThe existence of 40 cell types and the insolubility of lung collagen increase the complexity of identifying the types of collagen in lung and the cells responsible for the synthesis of each type. The techniques described here should eventually lead to a complete description of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…However, the recognition of collagen by lymphocytes from patients with fibrotic lung disease is not very specific; they do not distinguish between type I collagen of different species (human, rabbit) or different organs (lung, skin). Since prior studies have shown these type I collagens to be very similar (3,4,(26)(27)(28)(29), this cross-reactivity is not surprising.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the recognition of collagen by lymphocytes from patients with fibrotic lung disease is not very specific; they do not distinguish between type I collagen of different species (human, rabbit) or different organs (lung, skin). Since prior studies have shown these type I collagens to be very similar (3,4,(26)(27)(28)(29), this cross-reactivity is not surprising.…”
Section: Discussionmentioning
confidence: 61%
“…This is suggested by data demonstrating that: (a) collagen is bound to membranes of fibroblasts (41); (b) human lung fibroblasts synthesize type I collagen (28); and (c) antibodies to collagen are cytotoxic to fibroblasts in culture (42)(43)(44).…”
mentioning
confidence: 99%
“…4 Though [14C]-valine was specifically employed to detect the synthesis of elastin by the lung cells in culture, no radiactive band corresponding to proelastin or tropoelastin could be discerned in these cultures.29 Thus the guinea pig lung fibroblasts did not appear to synthesize any elastin under the conditions employed.…”
Section: Discussionmentioning
confidence: 97%
“…About 40% of lung cells are fibroblasts, which are the main producer of type I and III collagens (Hance et al, 1976). As cellular senescence of fibroblasts impairs the secretion of collagenous proteins due to the immediate intracellular collagen degradation (Martin et al, 1990;Shivakumar et al, 2003), an increased number of senescent fibroblasts can, at least in part, explain the lower biosynthesis of fibrillar collagens in the old mouse lung.…”
Section: Discussionmentioning
confidence: 99%